Localisation of two candidate genes for mental retardation using a YAC physical map of the Xq21.1-21.2 subbands. Issue 5 (May 1996) - Colleaux, L; May, M; Belougne, J; Lepaslier, D; Schwartz, C; Fontes, M
Abstract : Genetic studies in families with X linked mental retardation have suggested the location of several MR genes in the human q21 region. Since the establishment of cloned resources is an essential step towards the cloning of genes involved in inherited diseases, we built a yeast artificial chromosome (YAC) contig and an STS map of this part of the X chromosome. The contig, which extends from PGK1 in Xq13.3 to DXS1002 in Xq21.2, consists of 30 YACs mapped with 21 markers and spans about 6 Mb. The YAC contig was used as a framework to localise several previously known genes and CEPH/Genethon polymorphic markers, as well as to construct a physical map of the region surrounding one of these genes. We recently localised a presumed MR locus to the region flanked by DXS233 (proximal) and CHM (distal). In the present work, the zinc finger gene, ZNF6, has been shown to lie within this region and to be highly expressed in brain, making it a good candidate MR gene. Similarly the VDAC1 gene has been mapped between DXS986 and DXS72 and its candidate gene status for the Allan-Herndon-Dudley syndrome is discussed.